2008
DOI: 10.1159/000113517
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 and Interleukin-13 Enhance Human Bronchial Smooth Muscle Cell Proliferation

Abstract: Background: TH2 inflammation and bronchial smooth muscle cell (BSMC) hyperplasia are characteristic features of asthma, but whether these phenomena are linked remains unknown. This study aims to define the effect of the TH2 cytokines IL-4 and IL-13 on human BSMC proliferation when administered alone or in combination with the fibroblast growth factor 2 (FGF2) growth factor. In addition, the effects of the proinflammatory mediators TNFα and IL-1β and the involvement of members of the well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 44 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…In our study, nerve cells and smooth muscle cells (SMC) expressed IL-13Rα1, and SMC signalled in response to exogenous IL-13. IL-13, derived from KIR + cells, may drive muscle hyperplasia in CD by stimulating proliferation of SMC [6], so contributing to stricture formation [5]. We have also shown that nerve cells express IL-13 receptors and are increased in active UC and CD.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our study, nerve cells and smooth muscle cells (SMC) expressed IL-13Rα1, and SMC signalled in response to exogenous IL-13. IL-13, derived from KIR + cells, may drive muscle hyperplasia in CD by stimulating proliferation of SMC [6], so contributing to stricture formation [5]. We have also shown that nerve cells express IL-13 receptors and are increased in active UC and CD.…”
Section: Discussionmentioning
confidence: 63%
“…Fibroses in lung, liver and kidney have been linked to T cell synthesis of IL-13 [3]. This can promote collagen synthesis independently of TGF-β [4]; and cause smooth muscle cell proliferation [5], [6] and contraction [7], which may contribute to fibrotic stricture formation. IL-13 activates many other cells, including macrophages, mast cells, B cells and nerve cells (reviewed [8]), potentially contributing to pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that inflammatory cytokines such as IL-4 and IL-13 can contribute to goblet cell hyperplasia [15,16] and smooth muscle cell growth in vitro [17]. The lack of an association between goblet cell hyperplasia and airway smooth muscle layer on the one hand and IL-4 on the other hand in this study does not necessarily imply that this cytokine does not contribute to the remodeling process at all in our mouse models of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…An IL-13 induced role in goblet cell differentiation, mucus production, bronchial hyperresponsiveness, immunoglobulin E (IgE) synthesis (a switch of B cell antibody production) and the recruitment of eosinophils and basophils [14,15,16,17,18,19,20] has been repeatedly demonstrated [21]. …”
Section: The Role Of Il-13 and Il-4mentioning
confidence: 99%